Ultra-late triple metastasis to the breast, lung, and brain 25 years after nephrectomy for clear cell renal cell carcinoma: a case report and literature review - Xiao, Sujian; Wang, Xinyu; Deng, Xiaoling; Huang, Xin; Du, Chuance; Yuan, Huozhong; Li, Yanyan; Zhai, Qiliang (Frontiers in Oncology, 2026)
BackgroundClear cell renal cell carcinoma (ccRCC) most commonly metastasizes to the lungs, lymph nodes, bones, and liver. Metastasis to the breast is exceptionally rare, representing less than 0.5% of cases. Herein, we report an unprecedented case of triple metastasis with the longest recorded latency period.Case presentationAn 86-year-old female presented with a painless left breast mass 25 years after undergoing radical nephrectomy for ccRCC. Multi-modality imaging (mammography, ultrasound, MRI) revealed a suspicious breast lesion. Subsequent chest CT and PET-CT identified synchronous metastatic nodules in the lungs and brain. Histopathological examination of the resected breast mass confirmed metastatic carcinoma. The diagnosis of ccRCC metastasis was substantiated by an immunohistochemical profile positive for PAX8, CAIX, and CD10, while negative for estrogen receptor, progesterone receptor, and HER2.ConclusionThis case highlights breast metastasis as a rare but critical differential diagnosis in patients with a history of ccRCC, even decades after initial treatment. It underscores the necessity of lifelong follow-up for ccRCC survivors and demonstrates the integral role of imaging and pathological confirmation in guiding clinical diagnosis. Furthermore, the remarkable 25-year latency period challenges existing surveillance paradigms and provides a compelling rationale for the use of combined immunotherapy and targeted agents in managing ultra-late, multi-metastatic recurrences.